2018
DOI: 10.1038/s42003-018-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic ablation enables cancer cell targeting through pH modulation

Abstract: Minimally invasive ablation strategies enable locoregional treatment of tumors. One such strategy, electrolytic ablation, functions through the local delivery of direct current without thermal effects, facilitating enhanced precision. However, the clinical application of electrolytic ablation is limited by an incompletely characterized mechanism of action. Here we show that acid and base production at the electrodes precipitates local pH changes causing the rapid cell death that underlies macroscopic tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The literature on this subject explains that when two electrodes are immersed in a conductive medium and a direct current (galvanic current) passes between them, electrochemical reactions take place around the electrodes and in the medium containing the same. 5 The present study found that the pH change only takes place in a simple solution of NaCl. Using normal oxygenated Ringer's solution, no pH change was observed, neither did this occur with a live sample.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The literature on this subject explains that when two electrodes are immersed in a conductive medium and a direct current (galvanic current) passes between them, electrochemical reactions take place around the electrodes and in the medium containing the same. 5 The present study found that the pH change only takes place in a simple solution of NaCl. Using normal oxygenated Ringer's solution, no pH change was observed, neither did this occur with a live sample.…”
Section: Discussionsupporting
confidence: 52%
“…6 A pioneering work by Li et al 9 applied a GC protocol of 8.5 Volts at 30 mA during 69 minutes, obtaining changes in the concentrations of Na þ and K þ ions in the cathode (pH ¼ 12.9) and the Cl À concentrations in the anode (pH ¼ 2.1). Subsequently, several papers were published 5,7,10 that considered the pH change as being the main mechanism of necrosis in tissues treated with electrical currents. This change in pH within the human body requires a temporary application of $30 minutes to achieve these effects and also requires both electrodes to be present in the treated tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We used a 0.7% (w/v) agarose gel with a pH indicator (i.e., phenol red) for visualization of the ablation zone. Agarose gel was used since it is electrically neutral and mechanically stable at room temperature; this gel is a well-established phantom to assess EA 2,36,37 . The pH in the agarose gel was adjusted to a physiological pH of 7.4 by adding 0.9 wt/% sodium chloride.…”
Section: Ablation Zone Estimationmentioning
confidence: 99%
“…Local thermal ablation using insertable RF or microwave probes has also been used to destroy solid tumors in cases where the tumor is deemed to be nonresectable (e.g., liver or pancreatic tumors close to a sensitive anatomical structure) 1 . Although clinically accepted, thermal ablation methods face limitations in cases where the tumor is located near a major blood vein, for which collateral thermal damage is unacceptable [1][2][3] . Other ablation methods using laser sources, high-intensity focused ultrasound (HIFU), and cold (cryo-ablation) have also been proposed and are currently at various stages of development and clinical trials [4][5][6] .…”
mentioning
confidence: 99%
“…More recently, research conducted by Perkons et al [13] attempted to identify additional parameters by which EChT was able to destroy tumor growth. Three parameters were tested based the hypothesis of prior works: temperature, the presence of reactive oxygen species (ROS), and localized changes in pH value.…”
Section: The Evaluation Of Critical Parameters and Mechanismsmentioning
confidence: 99%